Supervision and Support of Primary and Secondary Education : A Policy Note for the Government of Poland - World Bank (Washington, DC, 2013)
This policy note examines how five countries: England, Finland, the Netherlands, New Zealand and the Republic of Korea organize the supervision and support of schools and teachers at the primary and secondary levels. Countries are compared and contrasted according to a framework consisting of seven aspects related to supervision. A workshop to discuss a draft version of this note as well as additional issues related to the overall organization of quality assurance systems in education and the Ministry's own current plans was held in Warsaw on May 10, 2010. The study found that there are a number of key issues in the provision of effective supervision and support. These include the issues of where to locate supervision and support institutionally, whether to keep these functions institutionally distinct or not, how to balance accountability and support, particularly given the need for accurate information, additional financial resources, and skilled human resources, and how to ensure the perceived legitimacy of the system.